Sustainable Agriculture and Green Economy: A Synergy for SDG 2 and SDG 13 - Umaira, Triana; Fajrian, Ade (Civil and Military Cooperation Journal, 2025)
Sustainable agriculture and the green economy play a crucial role in achieving Sustainable Development Goal (SDG) 2: "Zero Hunger" and SDG 13: "Climate Action." This study explores the synergy between sustainable agricultural practices and green economic strategies to enhance food security while mitigating climate change impacts. The research highlights the importance of transitioning towards environmentally friendly farming techniques, such as agroecology, precision agriculture, and resource-efficient farming, to ensure long-term sustainability. It also examines the challenges, including financial constraints, technological gaps, and policy inconsistencies, that hinder the large-scale implementation of sustainable agriculture. Furthermore, the study discusses innovative solutions, such as green finance and public-private partnerships, to support sustainable food production systems. By integrating sustainability principles into agriculture, this research provides insights into how food systems can become more resilient, equitable, and environmentally sustainable, aligning with global sustainability goals.